First observation of Bs 0→J/Ψf0(980) decays - Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alvarez Cartelle, P; Alves, A; Amato, S; et al. (2011)
Using data collected with the LHCb detector in proton-proton collisions at a centre-of-mass energy of 7 TeV, the hadronic decay Bs0→J/Ψf0(980) is observed. This CP eigenstate mode could be used to measure mixing-induced CP violation in the Bs0 system. Using a fit to the Π+Π- mass spectrum with interfering resonances gives Rf0/Φ≡Γ(Bs0→J/Ψf0,f0→Π+Π -)Γ(Bs0→J/Ψφ,φ →K+K-)=0.252-0.032-0.033+ 0.046+0.027. In the interval ±90 MeV around 980 MeV, corresponding to approximately two full f0 widths we also find R' ≡ Γ(Bs0→J/Ψf0,f0→Π+Π-)-980 Mev < 90 Mev)/Γ(Bs0→J/Ψφ,φ→K +K-)=0.162±0.022±0.016, where in both cases the uncertainties are statistical and systematic, respectively. © 2011 CERN.